Sex-Driven Differences in Immunological Responses: Challenges and Opportunities for the Immunotherapies of the Third Millennium. (4th March 2015) - Mirandola, Leonardo; Wade, Raymond; Verma, Rashmi; Pena, Camilo; Hosiriluck, Nattamol; Figueroa, Jose A.; Cobos, Everardo; Jenkins, Marjorie R.; Chiriva-Internati, Maurizio
<x xml:space="preserve">Abstract</x> Purpose of the study: Male-based studies, both at the biochemical and at the pre-clinical/clinical trial levels, still predominate in the scientific community. Many studies are based on the wrong assumption that both sexes are fundamentally identical in their response to treatments. As a result, findings obtained mainly in males are applied to females, resulting in negative consequences female patients. In cancer immunotherapy, there is still a scarce focus on this topic. Here we review the main differences in immune modulation and immune system biology between males and females with a particular focus on how these differences affect cancer immunotherapy and cancer vaccines. Methods: We reviewed articles published on PubMed from 1999 to 2014, using the keywords: sex hormones, immune response, estrogen, immunotherapy, testosterone, cancer vaccines, sex-based medicine. We also present new data wherein the expression of the cancer testis antigen, Ropporin-1, was determined in patients with multiple myeloma, showing that the expression of Ropporin-1 was influenced by sex. Results: Male and female immune systems display radical differences mainly due to the immune regulatory effects of sex hormones. These differences might have a dramatic impact on the immunological treatment of cancer. Moreover, the expression of tumor antigens that can be targeted by anti-cancer vaccines is associated with sex. Conclusion: Future clinical trials focusing on cancer immunotherapy will need to take into account the differences in the immune response and in the frequency of target antigen expression between male and females, in order to optimize these anti-cancer immunotherapies of the third millennium.